A influência do método de ensino para a aprendizagem de leitura - Piper, Francieli Kramer (2015)
Understanding how we learn how to read is a hot topic of investigation in the scientific field. Though there is research showing the more effective methods of teaching how to read, Brazilian schools and school policy makers do not adopt evidence-based methods for teaching. The goal of the present study was to investigate the process of teaching and learning how to read in the second grade of two elementary public schools of Porto Alegre/RS. The study investigated the relation between method used and student performance. Two reading tasks were applied: Test 1 (April/May) and Test 2 (August); the tests were carried out in two classes that applied distinct teaching methods. One class applied the Phonics Approach (MF) and the other, the Whole Language Approach (MG). Twenty-nine students participated of the research: 16 MF students and 13 MG students. In one of the tests, the students read excerpts from two books - Tom by André Neves and Adivinhe se puder by Eva Furnari to assess the level of reading; students were classified into 5 levels: pre-reading, decoding, syllabic reading, meaningful reading, and fluent reading. The second test was the Avaliação de palavras e pseudopalavras isoladas (SALLES, 2005): a list of 60 regular and irregular words and pseudowords (20 each). The tests results for the MF group were, in general, significantly better. In the first task, the variables reading time and reading level were evaluated; the results suggest MF students progressed better in terms of their reading level and reading time in the comparison between tests 1 and 2; MG students, in turn, also presented faster reading times, but the evolution of the reading level was less prominent than the MF group